Thought Presentation in Veronica Roth’s "Divergent": Stylistic Analysis - Josephine Vania Adiningtyas (Journal of English Language and Culture, 2020)
There are several ways to scrutinize literature. Indeed it is done according to the field of interests or needs. Linguistics is one of the fields that provides the way in analyzing literature through the perspective of a linguist, which is called stylistics. This research applies a stylistic approach using discourse as the language level, specifically seen through thought presentation in Divergent novel by Veronica Roth. This research endeavours: (1) to discover the types of thought presentation techniques used in the novel and (2) how thought presentation techniques reveal the language style of the author. The writer utilized purposeful sampling method since the first three chapters' data were selected and it presented the plot of why the author titled the novel 'Divergent.' Moreover, one of the aims in this research is to discover the style of the author. Thus the first three chapters were significant for the whole representative sampling. The data were categorized in the thought presentation techniques suggested by Leech and Short (2007) which are namely; Direct Thought (DT), Indirect Thought (IT), Free Direct Thought (FDT), Free Indirect Thought (FIT), and Narrative Report of Thought Acts (NRTA). Three thought presentation techniques were found in the analysis: Free Direct Thought (FDT) 83% and Free Indirect Thought (FIT) 11% and the least category is Narrative Report of a Thought Acts (NRTA) with 6% only. The study concludes that the employment of FDT and FIT as it occurred the most can reveal the author’s style. Roth’s style is dramatic since she employsfreer techniques, so that the readersget a vivid image of what is undergone by the characters. Thus, the thoughts produced obtain a high conscious quality.